Corrosion resistance of zinc–resin hybrid coatings obtained by electro-codeposition - Alina Crina Ciubotariu; Lidia Benea; Pierre Ponthiaux (Arabian Journal of Chemistry, 2019)
Pure zinc and zinc hybrid coatings containing phenol–formaldehyde resin particles were prepared by electrodeposition from zinc sulfate electrolytes. The effect of mean diameter size of particles on the morphology and topography of the surfaces was investigated by Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). It was shown that pure zinc coating has a regular surface, whereas the hybrid coating surfaces have fine surface structure. The corrosion resistance in 0.5 M sodium chloride was evaluated by potentiodynamic polarization and electrochemical impedance spectroscopy techniques. The polarization resistance calculated with both methods indicates that the electrochemical properties of conventional zinc coating were significantly improved by the incorporation of phenol–formaldehyde resin particles. Keywords: Zinc, Resin particles, Hybrid coatings, AFM, Electrochemical techniques, Polarization resistance